Sistem Rumah Cerdas berbasis IoT, TCP, dan Bluetooth - Abyanuddin Salam; Prengga Trisnanda (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2020)
Nowadays, improvement of technology is rapidly changing and improving, with the improvement of technology then there will be an impact. Electronic device control can be applied in the application of smart home system using electronic control device based on Internet of Things (IoT) and can be controlled remotely with the purpose of increasing efficiency, safety and comfort. This research has an objective to design and to make a system which can be accessed everywhere based on IoT. This research is using experimental methodology which use a WEMOS D1 mini as a master to act as a connector between hardware and software. Furthermore, Arduino Mega 2650 is used as a slave which is controlled by WEMOS D1 mini. Arduino Mega has a function to control the lighting and the gate system, while the installation isnside the house is controlled directly by the WEMOS D1 mini. Moreover, a Real Time Clock (RTC) is used for capturing data with a realtime of date and time. After that, the data will be uploaded into the firebase server, thinkspeak, and ubidots. In addition, the interface which is used is MIT App Inventor which has a function to control and monitor the system. The conclusion of this research is that the system accsess’ and control the house both inside and outside the house. Furthermore, the handphone application is already installed and can be used already. The solution when there are no internet connection in the house is that by using Bluetooth or TCP (Transmission Control Protocol) through the wifi inside the house.